Celebrating Canada. Volume 2, Commemorations, anniversaries, and national symbols - Blake, Raymond Benjamin; Hayday, Matthew, 1977- (Toronto : University of Toronto Press, 2018)
Popular and government-funded anniversaries and commemorations, combined with national symbols, play significant roles in shaping how we view Canada, and also provide opportunities for people to challenge the pre-existing or dominant conceptions of the country. Volume 2 of Celebrating Canada continues the scholarly debate about commemoration and national identity. Raymond B. Blake and Matthew Hayday bring together emerging and established scholars to consider key moments in Canadian history when major anniversaries of Canada's political, social, or cultural development were celebrated. The contributors to this volume capture the multiple and multi-layered meanings of belonging in the Canadian experience, investigate various attempts at shaping and re-shaping identities, and explore episodes of groups resisting or participating in the identity-formation process. By considering the small voices and those on the margins of Canada's many commemorative anniversaries, the contributors to Celebrating Canada reveal how important it is to think not only about anniversary moments but also about what they can tell us about our history and the shifting function of nationalism.
Introduction. Celebrating Canada: Commemorations, Anniversaries, and National Symbols -- 1 National Symbols and Commemorations: Analysing the Loyalist Centennial and the Conventions nationales acadiennes in New Brunswick in the 1880s -- 2 Emblemizing Canada in the Flag Debate of 1895 -- 3 Children of a Common Mother: The Rise and Fall of the Anglo-American Peace Centenary -- 4 Competing Pasts, Multiple Identities: The Diamond Jubilee of Confederation and the Politics of Commemoration -- 5 Bilingualism and Biculturalism at the Diamond Jubilee of Confederation, 1927 -- 6 Canada's Centennial Experience -- 7 A "Labor of Love in a Community Spirit" : The Cape Breton Miners' Museum and the Remaking of Historical Consciousness -- 8 Federal Funding, Local Priorities: Urban Planning and Ontario's Municipal Centennial Projects -- 9 Alternative Identities: The 1967 Centennial and the Campaign for a Better Canada -- 10 "Fit for Citizenship": Scouting and the Centennial Celebrations of 1967 -- 11 A Continental Centennial: Situating Expo 67 within the Canadian-American Relationship -- 12 New Nationalism in the Cradle of Confederation: Prince Edward Island's Centennial Decade -- 13 Conclusion: The Importance of Commemorations and National Symbols.
Includes bibliographical references.
Vendor-supplied metadata.
eBooks on EBSCOhost
Keywords: Holidays -- Canada; National characteristics, Canadian; Nationalism -- Canada; Canada -- Social life and customs; Jours fériés -- Canada; Fêtes nationales -- Canada; Canadiens; Nationalisme -- Canada; Canada -- Mœurs et coutumes; SOCIAL SCIENCE -- General; HISTORY / Canada / Post-Confederation (1867-); Holidays; Manners and customs; National characteristics, Canadian; Nationalism; Canada